Ectopic Kidney Mimicking Appendicular Abscess - Joseph, Danny Darlington Carbin (Niger J Surg, 2021)
Ectopic kidney is a congenital anomaly of renal position, which is commonly asymptomatic. Symptoms arising from pelvic kidneys can closely mimic pathological processes of nearby organs and vice versa. We report an 18-year-old girl who presented with acute onset of a painful lump in the right iliac fossa. Although the clinical features mimicked an appendicular abscess, the judicious use of cross-sectional imaging aided in the proper diagnosis. Pyonephrosis of a right-sided lumbar kidney was confirmed on further imaging and nephrectomy was performed. This case has been presented to highlight the significance of renal imaging in patients suspected of an appendicular abscess.